Therapeutic targeting of Aurora Kinase A in advanced prostate cancer - Bou Zerdan, Maroun; Asim Bilen, Mehmet; Yu, Jindan (Serican Journal of Medicine, 2025)
Prostate cancer (PCa) progresses from an androgen-dependent state to a castration-resistant form (CRPC) following androgen deprivation therapy (ADT), driven by adaptations that restore androgen receptor (AR) signaling. A subset of CRPC tumors evolves into neuroendocrine prostate cancer (NEPC), marked by AR independence, neuroendocrine marker expression, and poor prognosis. NEPC development is associated with genetic and epigenetic alterations, including loss of tumor suppressors (TP53, RB1) and activation of lineage plasticity pathways. Aurora kinase A (AURKA), a serine/threonine kinase regulating mitosis, is frequently overexpressed in NEPC and CRPC, promoting tumor aggressiveness. Recent studies highlight CXCR7's role in driving enzalutamide-resistant CRPC by activating AURKA through β-arrestin recruitment. Targeting AURKA with inhibitors like alisertib shows potential but is hindered by toxicity and patient variability, emphasizing the need for biomarkers to stratify responders.AURKA inhibition is synthetically lethal with RB1 or TP53 loss and may exploit vulnerabilities in tumors with homologous recombination defects, linking AURKA activity to resistance against DNA-damaging therapies, including PARP inhibitors, AR pathway inhibitors, and chemotherapy. Further investigation into AURKA alterations in CRPC/NEPC and their correlation with therapeutic outcomes may refine treatment strategies. Targeting AURKA holds promise for overcoming resistance and improving outcomes in aggressive, treatment-refractory PCa subtypes.